Robustness analysis and feedback stabilization of uncertain singular systems - Wang, Dianhui; Yu, Runyi (My University, 2004)
This paper studies complete stability robustness and feedback stabilization problem for uncertain singular systems. New perturbation upper bound that ensures the perturbed singular system remains completely stable (impulse-free and asymptotically stable) is derived. Analysis and examples show that the present result is less conservative than the previous ones. Based on an algorithm for eigenstructure assignment, a procedure to construct a state feedback matrix that maximizes the complete stability robustness bound of the closed-loop system is presented.
2004 5th Asian Control Conference --
Keywords: Asymptotic stability; Closed loop control systems; Eigenvalues and eigenfunctions; Feedback control; Matrix algebra; Perturbation techniques; Robustness (control systems); System stability; Feedback stabilization; Modulus matrix function; Singular systems; State-variable systems; Uncertain systems